Okvare zavedanja in odzivnosti po možganski poškodbi - kakšne možnosti ponuja metoda stimulacije globokih možganskih jeder? - Grabljevec, Klemen (Rehabilitacija (Ljubljana), 2012)
Improvements of emergency medicine enable a major part of comatose patients after severe brain injury to survive. After evolving from coma, some of them show no evidence of awareness of self and environment and give no meaningful response for the external stimuli; such condition is called a vegetative state. The reason lies in focal or widespread unilateral or bilateral injury of the central thalamic and parathalamic nuclei and rostrocaudal regions. In some patients, an inconsistent but cognitively mediated response to external stimuli can be observed, which is reproducible or sustained long enough to be differentiated from reflexive behaviour; such condition is called a minimally conscious state. With the deep brain stimulation method, usually the region of centromedian-parafascicular complex in dominant hemisphere is stimulated with implantable electrodes. The method showed to be effective in rare cases of patients in vegetative state to improve awareness and responsiveness to external stimuli and ability to communicate, but no improvement of motoric control was observed. There was more remarkable improvement in the group of patients in the minimally conscious state, who were able of independent ambulation and reached some degree of independence in daily activities.
Keywords: Brain Injuries; Deep Brain Stimulation; minimally conscious state; možgani; možganske poškodbe; poškodbe; rehabilitacija; Rehabilitation; stanje minimalne odzivnosti; stimulacija globokih možganskih jeder; vegetative state; vegetativno stanje; vocational rehabilitation